The taxonomy of factors of acceptance and use of technologies for human computer interface in digital services - Pintado, Pablo (2023)
Emerging technologies, e.g., cloud computing, artificial intelligence, robotics, and information technologies, facilitate digital transformation and promote digital services. Significant research exists on the acceptance and use of technologies and specific digital transformation (DT) practices. However, more research is needed to better understand user’s acceptance and how they use technology to better de-sign digital services. Thus, this paper: 1) proposes a Systematic Literature Review (SLR) of the models of acceptance and use of technologies, as well as of certain DT practices applied to the human-computer interaction (HCI) of digital services; 2) provides an analysis of the results of the behavior of the factors and practices; and 3) proposes a taxonomy of the acceptance and use factors applied to HCI of digital services by economic activity. The main contribution of this work is the proposed taxonomy in a vacancy area relevant to digital transformation efforts applied to digital services pursued globally, both in the private and public sectors.